Immunglobulin and Complement Levels in Schizophrenia and Affective Disorders - Kuloğlu, Murat; Bulut, Vedat; Atmaca, Murad; Önal, Süleyman; Geçici, Ömer; Tezcan, A. Ertan (Fırat University, 2002)
Objective: In this study, we aimed to examine the effects of schizophrenia and affective disorders on immunoglobulin and complement levels. Material and Methods: The study group was consisted of totally 48 patients diagnosed with schizophrenia (n=18), major depressive disorder (n=17) and bipolar disorder (n=13) according to DSM-IV. The control group was consisted of 33 healthy persons who applied to the Department of Psychiatry, College of Medicine at Firat University for driving licence examination and were evaluated to be normal. In both group, IgG, A, M, kappa, lambda, C3 and C4 were detected and compared between groups. Results: There were statistically significant differences with respect to IgG levels between control group and schizophrenia or depressive and bipolar disorder. With respect to C3, the levels were significantly higher in patients with depressive disorder than those with schizophrenia and controls and in patients with bipolar disorder than control group. There were no statistically significant differences among groups with respect to IgA, M and C4. Conclusion: The elevations in IgG and C3 levels support the association between immunologic system and psychiatric disorders. However, we consider that further investigations with large sample in which the drug use and the duration of illness are taken into consideration should be rule out are required.

Amaç: Çalışmamızda; şizofreni ve duygudurum bozukluklarının immünglobulin ve kompleman düzeyleri üzerine etkilerinin araştırılması amaçlandı. Gereç ve Yöntem: Çalışma grubunu Fırat Üniversitesi Tıp Fakültesi Psikiyatri polikliniğine başvuran ve DSM-IV tanı ölçütlerine göre şizofreni (s=18), major depresif bozukluk (s=17) ve bipolar bozukluk (s=13) tanısı konulan toplam 48 hasta ve ehliyet muayenesi için başvurarak klinik muayene sonucu psikiyatrik bozukluk belirlenmeyen 33 sağlıklı birey kontrol grubunu oluşturmuştur. Her iki grubun IgG, IgA, IgM, κ, λ, C3 ve C4 düzeyleri belirlenerek birbirleriyle karşılaştırıldı. Bulgular: IgG düzeyleri şizofreni, depresif bozukluk ve bipolar bozukluk tanısı konanlarda kontrol grubuna göre anlamlı olarak yüksek bulundu. C3 düzeyleri depresif bozukluk tanısı konanlarda, şizofreni tanısı konanlardan ve kontrol grubundan; bipolar bozukluk tanısı konanlarda kontrol grubundan anlamlı olarak yüksek bulundu. IgA, IgM ve C4 düzeyleri yönünden gruplar arası fark saptanmadı. Sonuç: IgG ve C3 düzeyi yönünden belirlediğimiz yükselmeler immünolojik sistemin psikiyatrik bozukluklarla ilişkisini destekler niteliktedir. Ancak, geniş hasta gruplarıyla ve ilaç kullanımı ile hastalık süresinin de gözönünde bulundurulduğu çalışmaların yararlı olacağı kanısındayız.
ŞİZOFRENİ VE DUYGUDURUM BOZUKLUKLARINDA İMMÜNGLOBULİN VE KOMPLEMAN DÜZEYLERİ